Effect of L- Arginin on Placental Hipoxia Inducible Factor -1-Alpha (HIF-1-A) Expression at Preeclampsia Mice Models - Anggraini, Nutria Widya Purna; Sulistyowati, Sri; Pramono, Besari Adi; Kristanto, Herman (Indonesian Journal of Medicine, 2020)
Background: Placental hypoxia is one of the theories that cause preeclampsia. In placental hypoxia of preeclampsia, there is an increase of Hipoxia Inducible Factor 1 Alpha (HIF-1-A) expression as a response to hypoxia. L-Arginine administration through the L-Arginine-Nitric Oxide pathway is expected to improve placental hypoxia. This study aimed to examine the effect of L- Arginin on placental HIF-1-A expression at preeclampsia mice models.Subjects and Method: Experimental study with parallel group post-test only design. The study was carried out at the Veterinary Medicine Faculty of Airlangga University. Thirty six preeclampsia mice models were made with intravenous injection 10ng anti-Qa-2 on day 1-4 of pregnancy. They were divided into 2 groups: (1)18 mice without treatment (control) and (2) 18 mice were given L-Arginin 200 mg/kgBW/day on day 7-15 of pregnancy. They were terminated on day 16 then immunohistochemistry examination of HIF-1-A expression was done on the placental samples. The dependent variable was placental Hipoxia Inducible Factor-1-Alpha (HIF-1-A) expression. The independent variables were L-Arginin administration. HIF-1-A expression was measured by H-Score method. The data were analyzed by t-test. Results: The mean of placental HIF-1-A expressions of treatment group was lower (Mean= 7.98; SD=9.35) than control group (Mean=41.95; SD= 32.20), and it was statistically significant (p <0.001).Conclusion: L-Arginin reduces the Placental Hypoxia Inducible Factor Alpha (HIF-1-A) expression on preeclampsia mice model.Keywords: L-Arginine, HIF-1-A, PreeclampsiaCorrespondence: Nutria Widya Purna Anggraini. Department of Obstetrics and Gynecology, Faculty of Medicine Universitas Sebelas Maret/ Dr. Moewardi General Hospital Surakarta. Jl Kolonel Sutarto 132, Surakarta, Central Java, Indonesia. Email: nutria_dr@staff.uns.ac.id. Mobile: 08122651819.Indonesian Journal of Medicine (2020), 05(03): 191-199https://doi.org/10.26911/theijmed.2020.05.03.03